Happy birthday, Big Bad Wolf - Asch, Frank (Toronto, ON ; Tonawanda, NY : Kids Can Press, 2011)
The Pig family tries to confuse the Big Bad Wolf by throwing him a surprise birthday party, but it is not actually Wolf's birthday and the scheme might not be enough to keep the pigs from becoming Wolf's main course.
3.3
Preschool
Preschool
Keywords: Birthday parties -- Juvenile fiction; Swine -- Juvenile fiction; Wolves -- Juvenile fiction; Birthday parties -- Fiction; Pigs -- Fiction; Wolves -- Fiction; Birthday parties -- Fiction; Pigs -- Fiction; Wolves -- Fiction; Picture books for children